Efeito dos processos de aquisição sobre a eficiência ambiental em instituições federais de ensino superior - Vaz, Caroline Rodrigues (2010)
This work had as objective analyzes the influence of the processes of acquisitions and storages of consumption goods on the environmental efficiency in the Federal Institutions of higher education (IHE). This research is of basic nature, of approach of the qualitative and quantitative problem, under the point of view of your exploratory and descriptive objectives and of your technical procedures as bibliographical and of rising. Researches were accomplished in the Federal Government's legislations on the processes of goods/services acquisitions. The data were collected in a representative institution of IHES through structured questionnaires, being destined to managers and servers requisiteness. The chosen place was the Federal Technological University of Paraná, Campus Ponta Grossa, where it took place observation in loco of the operation of the system and of the process bidding. For the analysis of the data it was used to the tool environmental Cleaner Production presenting the global flowchart of the processes, analysis of the demand/costs and residues, the levels of prioritization of generation of residues and the identification of the indicators of environmental acting. It identified that the indicators of environmental acting that more she highlighted they were time/acquisition, costs/quality and losses/validity. In which was chosen two markers, a typically of administrative and educational and other consumption characteristic of the activities of Research and Extension. The consumption materials selected they were the paper and chemical reagents, respectively. The paper and the chemical reagents presented significant losses for due validity, packing material and maintenance. On this, it is evaluated the possible causes of the losses and the influence of the Law 8666/93. It saw her that the Law 8.666/93 brings positive points for the Public Administration, but at the same time it was evidenced that your application can induce, carting losses in the Environmental Efficiency of an Institution. Subjects administrative excesses in the legal applications, the lack of specific knowledge on the part of involved them in the acquisition processes (of the demand to the storage), the lack of trainings, the absence in “real time” of answers to legal doubts and the difficulty of vision systemic of the legislation together with the institutional internal system; they are some of the lifted up elements.